Clean electricity through advanced coal technologies - Cheremisinoff, Nicholas P. (William Andrew, 2012)
Clean Electricity Through Advanced Coal Technologies focuses on the environmental damages caused by power plant operations and the environmental issues with solid waste, air and impoundment issues such as the massive TVA spill in Kingston, TN.